MULTIMODAL TASKS USING DIGITAL STORYTELLING IN EFL CLASSROOMS: A NARRATIVE LITERATURE REVIEW - Hasibuan, Kalayo; Ahmad Putri, Farhana Afifah; Al-Qusairi, Imam; Nuraini, Lutfia; Alfath, M Jihad Sabilillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of multimodal tasks and digital storytelling has emerged as a significant pedagogical approach in English as a Foreign Language (EFL) education. This article undertakes a narrative literature review to examine how multimodal tasks incorporating digital storytelling have been implemented in EFL classrooms, what theoretical frameworks underpin their use, and what benefits and challenges have been documented in the literature. Drawing on 30 studies published between 2015 and 2025 from Scopus, DOAJ, and Google Scholar, this review identifies three major themes: (1) the role of multimodality in enhancing language acquisition, (2) digital storytelling as a bridge between cultural and communicative competence, and (3) the pedagogical and technological challenges of implementation. Findings reveal that multimodal digital storytelling tasks significantly improve learners' speaking, writing, and intercultural competence, while also fostering creative and critical thinking skills. However, unequal access to technology, limited teacher training, and insufficient time allocation remain persistent barriers that must be addressed to ensure equitable implementation of multimodal instruction in EFL contexts.